3D constraints and finite-difference modeling of massive sulfide deposits: The Kristineberg seismic lines revisited, northern Sweden - Dehghannejad, M.; Malehmir, A.; Juhlin, Christopher; Skyttä, P. (2012)
The Kristineberg mining area in the western part of the Skellefte ore district is the largest base metal producer in northern Sweden and currently the subject of extensive geophysical and geologic studies aimed at constructing 3D geologic models. Seismic reflection data form the backbone of the geologic modeling in the study area. A geologic cross section close to the Kristineberg mine was used to generate synthetic seismic data using acoustic and elastic finite-difference algorithms to provide further insight about the nature of reflections and processing challenges when attempting to image the steeply dipping structures within the study area. Synthetic data suggest processing artifacts manifested themselves in the final 2D images as steeply dipping events that could be confused with reflections. Fewer artifacts are observed when the data are processed using prestack time migration. Prestack time migration also was performed on high-resolution seismic data recently collected near the Kristineberg mine and helped to image a high-amplitude, gently dipping reflection occurring stratigraphically above the extension of the deepest Kristineberg deposit. Swath 3D processing was applied to two crossing seismic lines, west of the Kristineberg mine, to provide information on the 3D geometry of an apparently flat-lying reflection observed in both of the profiles. The processing indicated that the reflection dips about 30° to the southwest and is generated at the contact between metasedimentary and metavolcanic rocks, the upper part of the latter unit being the most typical stratigraphic level for the massive sulfide deposits in the Skellefte district.